Gestational Hypertension and Organophosphorus Pesticide Exposure: A Cross-Sectional Study. (3rd August 2015) - Ledda, Caterina; Fiore, Maria; Santarelli, Lory; Bracci, Massimo; Mascali, Giuseppe; D'Agati, Maria Grazia; Busà, Alfredo; Ferrante, Margherita; Rapisarda, Venerando
Abstract : Hypertension is the most common medical problem encountered during pregnancy, complicating 2-3% of pregnancies. High blood pressure (BP) with diastolic BP ≥ 90 mm Hg and/or systolic BP ≥ 140 mm Hg arising after week 22 of pregnancy and resolving after delivery is defined as gestational hypertension (GHY). The aim of this cross-sectional study was to investigate whether occupational and/or environmental exposure to organophosphorus (OP) pesticide affects GHY. Women at approximately 22 weeks of gestation were recruited. OP pesticide exposure in the first trimester of pregnancy was classified into four categories: no exposure, indirect exposure, domestic exposure, and occupational exposure. Application of the exclusion criteria left 2203 participants (mean age 30.4 ± 11.6 years). Data analysis showed that in women with indirect OP pesticide exposure the incidence of GHY was slightly higher than that in the world population, whereas domestic exposure involved a 7% increase and occupational exposure a 12% increase. Analysis of the pesticides used by participants highlighted a possible role for malathion and diazinon (adjusted OR 1.09 and 1.14, resp.). Further investigation of exposed workers and the general population is clearly warranted given the broad diffusion of OP pesticides and their possible public health impact, maybe by including a wider range of health outcomes.